Report of Acineta euchaetae Sewell, 1951 from new locality of the Arabian Sea with notes on their taxonomy and distribution - Chatterjee, Tapas; Dovgal, Igor; Fernandes, Veronica; Bhaumik, Amrita; Nanajkar, Mandar (Zootaxa, 2021)
The article deals with the data about new find of the rare suctorian species Acineta euchaetae Sewell, 1951 on calanoid copepod host Euchaeta marina (Prestandrea, 1833) from the Arabian Sea. Seven young (sub-adult) individuals of the ciliate were observed on rear part of cephalothorax and on abdomen of adult male of copepod. The data about all known finds of A. euchaetae are discussed as well as the information on different developmental stages of the ciliate species. It is suggested that A. euchaetae is euryhaline species distributed in Eurasian coastal and inland waters and have preference for calanoid copepod hosts, but do not show specificity to any calanoid genus or species. The summarized diagnosis and refined systematic position of A. euchaetae are also provided.